2019
DOI: 10.1128/jvi.01479-18
|View full text |Cite
|
Sign up to set email alerts
|

GII.4 Norovirus Protease Shows pH-Sensitive Proteolysis with a Unique Arg-His Pairing in the Catalytic Site

Abstract: Human noroviruses (NoVs) are the main cause of epidemic and sporadic gastroenteritis. Phylogenetically, noroviruses are divided into seven genogroups, with each divided into multiple genotypes. NoVs belonging to genogroup II and genotype 4 (GII.4) are globally most prevalent. Genetic diversity among the NoVs and the periodic emergence of novel strains present a challenge for the development of vaccines and antivirals to treat NoV infection. NoV protease is essential for viral replication and is an attractive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 59 publications
(54 reference statements)
2
21
1
Order By: Relevance
“…However, a neighbouring dimer in the crystal structure forms an interface of comparable buried surface area (692.3 Å 2 ) between chains labelled A and D chains and likewise for chains labelled the B and C. This result indicates that higher order oligomers may possibly be formed by SV3CP dimers, such as the putative tetramer shown in Fig. 1 b. Intriguingly, a number of other human GI and GII noroviral protease structures ( Nakamura et al, 2005 , RCSB ID: 1wqs; Muzzarelli et al, 2019 , RCSB ID: 6b6i; Viskovska et al, 2019 , RCSB ID: 6nir) form essentially the same tetrameric assembly in the crystals, as shown in Supplementary Fig. 1 .…”
Section: Resultsmentioning
confidence: 78%
“…However, a neighbouring dimer in the crystal structure forms an interface of comparable buried surface area (692.3 Å 2 ) between chains labelled A and D chains and likewise for chains labelled the B and C. This result indicates that higher order oligomers may possibly be formed by SV3CP dimers, such as the putative tetramer shown in Fig. 1 b. Intriguingly, a number of other human GI and GII noroviral protease structures ( Nakamura et al, 2005 , RCSB ID: 1wqs; Muzzarelli et al, 2019 , RCSB ID: 6b6i; Viskovska et al, 2019 , RCSB ID: 6nir) form essentially the same tetrameric assembly in the crystals, as shown in Supplementary Fig. 1 .…”
Section: Resultsmentioning
confidence: 78%
“…A previous study reported that the amino acids adjacent to the active sites in the Pro protein of enterovirus 71 play a crucial role in protease activity based on the reduction of activity caused by the mutations of the residues (Wang et al, 2011). Moreover, Viskovska et al (2019) reported that the NoV GII protease showed activity in a pH-dependent manner by interactions between the residues H30 and R112. In this study, we found that these amino acids were conserved in most GII genotypes, except for GII.P25 ( Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted into the development of drug candidates (Hussey et al, 2011;Muhaxhiri et al, 2013;Muzzarelli et al, 2019;Viskovska et al, 2019). A recent report demonstrated different effectiveness of antivirals against GI and GII NoVs, suggesting that the amino acid diversity in Pro may result in different effectiveness of drugs (Viskovska et al, 2019). It is important to understand the evolution of the Pro region of GII NoV, because this virus is the predominant genogroup in patients with NoV infection.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the GII.4 protease crystal structure shows that this protein presents changes in the S2 substrate-binding pocket and the active site (catalytic triad residues) compared to those sites in the GI homologous protein. Another characteristic of the active site of the GII.4 protease is that there is a conserved arginine that interacts with the catalytic histidine, which restricts the access of inhibitors or substrates to the S2 pocket and makes the proteolytic activity of this protease sensitive to pH changes (75). Thus, the GI protease inhibitors may not be effective for the GII.4 protease.…”
Section: Proteasementioning
confidence: 99%
“…However, the ProPol precursor has two enzymatic functions: protease and polymerase activities. It should be noted that the ProPol complex has a higher enzymatic performance compared to the activity of both proteins separately (75,77,90). Subsequently, the three precursors are cleaved by the action of the ProPol complex, which in turn self-cleaves and generates the six individual non-structural proteins.…”
Section: The Replicative Cycle Of Hunovmentioning
confidence: 99%